(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence of gingivitis and the need for gingivitis treatment among older adults in selected localities of Ha Nam Province in 2024. Methods: A retrospective descriptive study was conducted using 316 oral health examination records of older adults collected by the Ha Nam Provincial Center for Disease Control in 2024. Data were extracted from archived records and entered and analyzed using descriptive statistical methods. Results: The prevalence of gingivitis among older adults was 79.7%. No statistically significant differences in gingivitis prevalence were observed between males and females or among age groups. The proportion of older adults reporting a need for gingivitis treatment was 39.3%, with a significantly higher treatment need among females compared with males. Conclusion: Gingivitis is highly prevalent among older adults in Ha Nam Province, while the perceived need for treatment remains low. These findings highlight the need to strengthen health communication, prevention, and gingivitis management within community-based oral health care for older adults.